Swot Analysis: Optimization Of Free Trade Zone KPPB Sabang As Shore Base Port - Adnan Adnan; Amiruddin Amiruddin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Free trade practices are formed based on agreements, which are binding on the parties and must be implemented in good faith. KPBPB Sabang is an area within the jurisdiction of the Republic of Indonesia which is separate from the customs area so that it is free from import duties, value added tax, sales tax on luxury goods, and excise (fiscal and non-fiscal incentives). KPBPB Sabang has the potential to become a shore base port to support the oil and gas (oil and gas) industry off the coast of Aceh, and oil and gas exploration activities in the Andaman (Sea) Block. Through SWOT analysis, the Sabang area has great potential to become a connectivity hub because it has met the minimum requirements. However, the synergy between regulations, facilities and services at KPBPB Sabang still needs to be improved, both as a multi-purpose port and as a shore base port.